Design and Calculation of Braking System for High-Speed Train Operating at 160 km/h - Mohammad Samsul Bakhri; Muhammad Nuzan; Hamzah Ali Nashirudin (Lembaga Pengembangan Kinerja Dosen, 2024)
The transport industry stands out as a crucial domain in bolstering Indonesia's journey toward economic revitalization, swift progress, and equitable distribution. At present, Indonesia is in the process of establishing a high-speed railway sector that adheres to global benchmarks. Rail-based transit systems exert considerable influence on the mobility of both individuals and commodities. Trains possess the capacity to convey substantial volumes of commuters and freight in one journey, thereby playing a role in diminishing operational expenses for transportation fleets. Braking is an important aspect of driving because it affects safety, vehicle control, and vehicle efficiency. In order to develop braking research, high-speed train braking test equipment is needed to describe the actual conditions during braking. High-speed trains are a type of train capable of traveling at speeds above 200 km/h. The braking applied to these high-speed trains involves several combined forces, including regenerative braking and pneumatic braking. In regenerative braking, deceleration occurs due to the conversion of kinetic energy into electrical power. This mechanism is carried out when the train is at an operational speed of 220 km/h until it decelerates to 160 km/h. Next, pneumatic braking was applied at a speed of 160 km/h until the train slowed down and came to a stop. This study shows how the calculation process was carried out using a scale of 1:4 at a speed of 160 km/h.